The Influence Of Workload And Compensation On Employee Performance At PT. Honda Autobest Service Department - Yayang Oki Prasetio; Gumilar, Dedi (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this study was to determine the effect of workload and compensation on employee performance at PT Honda Autobest Service Department, both partially and simultaneously. The population in this study were all employees at PT Honda Autobest service department. which amounted to 30 employees. The sampling technique used in this research is the saturated sampling technique. The method used in this research is a quantitative method with data collection techniques used are interviews and distribution of questionnaires to respondents. The data analysis technique used is multiple linear regression using the SPSS program. The findings of the study concluded that: (1) Workload has a significant effect on employee performance. (2) Compensation has a significant effect on employee performance. In the simultaneous test, workload, and compensation have a positive and significant effect on employee performance at PT Honda Autobest Service Department. The magnitude of the influence of workload and compensation is indicated by the value. Adjusted R Square of 28.2%. and the remaining 71.8% is influenced by other variables not examined in this study.